Ḥarakāt Al-Ṭawā‘if al-Bāṭinīyah al-Indūnīsīyah qabla Indiwā’iha that Ri‘āyati al-Tarbīyah wa al-Thaqāfah - M. Ghufron Zainul Alim (Studia Islamika, 1995)
It is inevitable that the presence of Islam in the archipelago little more spark religious conflict in the region . Local people have been accustomed to living in a Hindu - Buddhist teachings systems for centuries . The influence of these religions not only revolves around the ritual affairs , but has its roots in various aspects of life . The establishment then faltered when Islam comes to offer a different concept of life . Through the history of data it can be seen how the Majapahit kingdom must bow to the Demak kingdom held by Muslims . Of course not all conflicts arise in the form of political infighting . Conflict between Hindu - Buddhist and Islam can also appear in literary expression . In those days , such as the writings appear Gatoloco Fiber or Fiber Darmogandul , which clearly indicates the existence of tensions or religious conflicts . The word " God " for example , in the Java language spoofed " olo " which means ugly . "The Messenger " ( messenger of Allah ) was changed to " guilt " ; and Muhammad equated with Javanese term meaning " tomb " which means grave .DOI: 10.15408/sdi.v2i2.838